(untitled) (Global Journal of Science Frontier Research, 2020)
Here, we report a summary of some works already published. We highlight the existence of a new paradigm in physics of hadrons, based on the idea that quarks, and hadrons are geometric structures of coupled quantum oscillators. The geometric form is "Aurea" (golden), and, so, the representative model is called Aurum Geometric Model (AGM). To realize these structures, the quantum oscillators must be to structure at sub-oscillators, and half-quanta (IQO). To a structure-particle, we associate a structure equation, and, by, an appropriate mathematic procedure, we find the values of hadronic masses, like quarks, mesons, and nucleons.